Study on water quality at Sg. Pandan, Kuantan, Pahang - Naimah Mardhyyah, Che Mat (2012)
Sungai (Sg.) Pandan is a one of the recreational area in Pahang where it always full with visitors from various places. Study has been carried out in order to identify the water quality and it suitability as raw drinking water of Sg. Pandan at Panching area. This water quality study was conducted to determine and to analyze some of water quality parameter that had been chosen (temperature, pH, dissolved oxygen, turbidity, total coliform, hardness, biological oxygen demand, chemical oxygen demand, nitrate and total suspended solid). All the parameters involve were compared to the Interim National Water Quality Standard (INWQS) and National Guidelines for Raw Drinking Water Quality provided by the Department of Environment (DOE). From the results, all parameters except BOD was compared to INWQS and classified as CLASS JIB. The BOD value was higher than the standard limit and classified as CLASS IV. From the results, the water can be used as a raw source after being treated.